β1-Subunit of the calcium-sensitive potassium channel modulates the pulmonary vascular smooth muscle cell response to hypoxia - Barnes, Elizabeth A. (Am J Physiol Lung Cell Mol Physiol, 2018)
Accessory subunits associated with the calcium-sensitive potassium channel (BK(Ca)), a major determinant of vascular tone, confer functional and anatomical diversity. The β1 subunit increases Ca(2+) and voltagesensitivity of the BK(Ca) channel and is expressed exclusively in smooth muscle cells. Evidence supporting the physiological significance of the β1 subunit includes the observations that murine models with deletion of the β1 subunit are hypertensive and that humans with a gain-of-function β1 mutation are at a decreased risk of diastolic hypertension. However, whether the β1 subunit of the BK(Ca) channel contributes to the low tone that characterizes the normal pulmonary circulation or modulates the pulmonary vascular response to hypoxia remains unknown. To determine the role of the BK(Ca) channel β1 subunit in the regulation of pulmonary vascular tone and the response to acute and chronic hypoxia, mice with deletion of the Kcnmb1 gene that encodes for the β1 subunit (Kcnmb1(−/−)) were placed in chronic hypoxia (10% O(2)) for 21–24 days. In normoxia, right ventricular systolic pressure (RVSP) did not differ between Kcnmb1(+/+) (controls) and Kcnmb1(−/−) mice. After exposure to either acute or chronic hypoxia, RVSP was higher in Kcnmb1(−/−) mice compared with Kcnmb1(+/+) mice, without increased vascular remodeling. β1 subunit expression was predominantly confined to pulmonary artery smooth muscle cells (PASMCs) from vessels ≤ 150 µm. Peripheral PASMCs contracted collagen gels irrespective of β1 expression. Focal adhesion expression and Rho kinase activity were greater in Kcnmb1(−/−) compared with Kcnmb1(+/+) PASMCs. Compromised PASMC β1 function may contribute to the heightened microvascular vasoconstriction that characterizes pulmonary hypertension.